Allergic contact dermatitis pattern in Kuwait: nickel leads the pack. In-depth analysis of nickel allergy based on the results from a large prospective patch test series report - Almutairi, Nawaf; Almutawa, Fahad (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Contact dermatitis is a relatively common dermatosis reported among several population groups from all around the globe. However, the data from Kuwait is unavailable. Patch tests are essential for the diagnosis of contact sensitization. Aim : To determine a relative frequency and pattern of sensitizers to different allergens in patients of suspected contact dermatitis in Kuwait and, also to study the role of the commonest sensitizer in detail. Material and methods: Patch tests were performed in 2461 consecutive patients with a clinical diagnosis of contact dermatitis seen at our hospital between September 1, 2014 and August 31, 2015. Out of the total of 1381 (56.1%) patients with positive patch test results to at least one allergen, 546 (22.2%) patients with a single positive reaction to nickel only (single largest sensitizer) were selected as the study population for further detailed analysis. Results : At least one positive patch test reaction was found in 1381 (56.12%) patients. Nickel was found to be the most common sensitizer seen in 546 (40%) patients. The mean age was 37.3 ±13.8 years and the mean duration of disease was 27.3 ±13.8 months. Most (387/546) patients sensitized were females. The forearms/hands and wrists were the most prevalent sites (52.56% of the participants). In 58.91% of women, dermatitis was more often confined to other sites, mostly ears and the neck due to earrings and necklaces. Just more than half of the number (51.09%) of nickel allergic patients were found in the age group of 15–25 years. Hairdressers/beauticians were the most affected group followed by house workers (housewives, cleaners, housekeepers). Conclusions : Nickel is the single most common sensitizer found in our patients, and female sex, young age, occupation with long hours of contact to nickel are high risk factors. We recommend that a directive, which limits the release of nickel from products with extended skin contact, be approved in Kuwait.